Pengembangan UMKM Rengginang Bu Anik Melalui Strategi Branding - Natasya Anggraeni; Eko Purwanto (jurnal ABDIMAS Indonesia, 2023)
This Community Service activity aims to analyze the role of branding in the success of the Rengginang Bu Anik UMKM. The Community Service Activity method used is qualitative, by combining in-depth interviews, participatory observation, and content analysis. The results of Community Service Activities show that branding plays a significant role in building a positive image and reputation for MSMEs and differentiating themselves from competitors. The process of establishing a brand identity, selecting visual elements, logos and packaging that support the brand image, as well as the use of social media and online marketing have a positive impact on the success of MSMEs. Apart from that, an effective communication strategy and the influence of branding on increasing sales and business growth also proved important in the context of Rengginang Bu Anik. However, this Community Service Activity also identified several obstacles faced by MSMEs in implementing branding strategies, such as limited resources and a lack of understanding of the importance of branding. Therefore, solutions and recommendations are provided to overcome these challenges and take advantage of opportunities in developing MSME brands. This Community Service activity provides in-depth insight into the role of branding in the success of MSMEs and can provide practical guidance for other MSMEs in developing their brand.